2002
DOI: 10.1038/sj/cgt/7700399
|View full text |Cite
|
Sign up to set email alerts
|

In situ adenoviral interleukin 12 gene transfer confers potent and long-lasting cytotoxic immunity in glioma

Abstract: Interleukin 12 ( IL -12 ) is a cytokine that promotes an antitumor Th1 -type pattern of differentiation in mature naïve T cells. Despite its therapeutic success in multiple animal models of cancer, the utility of systemically administered recombinant cytokine has been limited by its toxicity. This has encouraged the development of local IL -12 delivery systems through gene transfer. To determine the effect of local adenoviral delivery of IL -12 on glioma immunogenicity, mice bearing GL -26 gliomas in the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
(13 reference statements)
0
14
0
Order By: Relevance
“…22 Use of a high-titer adenoviral vector encoding IL-12 is another strategy that was reported to induce antitumor responses in a glioma model. 23 Previous studies indicated that transfection of genomic DNA from the malignant cells into a fibroblast cell line resulted in stable integration and expression of the transferred DNA. 24,25 Both the genotype and the phenotype of the cells that took up the exogenous DNA were altered as portions of the transferred DNA were expressed.…”
Section: Discussionmentioning
confidence: 99%
“…22 Use of a high-titer adenoviral vector encoding IL-12 is another strategy that was reported to induce antitumor responses in a glioma model. 23 Previous studies indicated that transfection of genomic DNA from the malignant cells into a fibroblast cell line resulted in stable integration and expression of the transferred DNA. 24,25 Both the genotype and the phenotype of the cells that took up the exogenous DNA were altered as portions of the transferred DNA were expressed.…”
Section: Discussionmentioning
confidence: 99%
“…The use of IL-12 has generated significant interest in the field of tumor immunotherapy and on the basis of successful results obtained in preclinical models has been tested in Phase I and II clinical trials [13][14][15][16][17]. Several approaches have focused on the local release of IL-12 at the site of a tumor via methods including IL-12 transfected fibroblasts or DC [18] [19], in vivo transfection of tumor cells via viral vectors [20][21][22][23][24][25][26], or electroporation of plasmid DNA [4,[27][28][29][30]. Beyond the technical complexities and potential complications of these approaches, the clinical results have been disappointing and have dampened enthusiasm for intratumoral cytokine-based immunotherapies.…”
Section: Discussionmentioning
confidence: 99%
“…One major immunotherapeutic approach involves the gene transfer of immune-stimulating cytokines including IL-4, IL-12 and Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL). Infiltrating immune cells were found in brain tumors but their function can be modified by tumor-derived immuno-suppressors such as TGF-β [97], IL-10 [98] and Fas ligands [99], and earlier studies have used immunestimulating cytokines IL-4 [100] or IL-12 [101,102] to overcome immunosuppression by these suppressive molecules produced by cancer cells.…”
Section: Immunotherapy For Brain Tumorsmentioning
confidence: 99%